The motivation and actions of Australians concerning brain health and dementia risk reduction. (27th July 2015) - Smith, Ben J.; Ali, Suha; Quach, Henry
Abstract : Issue addressed: Alzheimer's disease and dementia are recognised as critical public health priorities. This study investigated intentions and behaviours concerning brain health and dementia risk reduction among Australians. Methods: A cross‐sectional survey of 1000 persons aged 20–75 years measured knowledge, beliefs, intentions and behaviours concerning brain health and dementia. The demographic, experiential and cognitive factors associated with intentions and actions were examined. Results: Around half of respondents were motivated to improve brain health. Behaviours most often reported were mental activity (19%), physical activity (9.6%) and dietary action (6.5%). Actions were most likely among women (OR 1.59, 95% CI 1.19–2.14), those aged 60 years and over (OR 3.07, 95% CI 2.01–2.58), with university education (OR 1.67, 95% CI 1.08–2.58) or with prior contact with a person with dementia (OR 1.99, 95% CI 1.12–3.56). Both intentions and actions were associated with moderate to high knowledge, and beliefs and confidence that favoured dementia risk reduction. Conclusions: A lower proportion of Australians reported taking action to improve brain health than who expressed intentions in this regard. Strategies are needed to improve knowledge about the range of behaviours that contribute to dementia risk reduction and to increase confidence that this outcome is personally achievable. So what?: The burden of disease due to Alzheimer's disease and dementia is growing dramatically. It is essential to promote awareness that dementia is not an inevitable result of ageing and to increase understanding that action can be taken throughout the life course to promote brain health.